Dynamic value of slab sectors sectioned by papillotomy and sphincterotomy: electromanometric study of the Oddian corridor - Cosco Montaldo, Homero; Bustos, Raúl; Píriz, Héctor; Seigal, Julio (Cirugía del Uruguay, 2021)
For the first time the dynamic value of the Oddian .corridor in man is documented through the use of simultaneous electromanometric registers of the duodenum and the Oddian channel. The base level of the duodenum is shown to· be inferior to that of the Oddi, thus disproving that it is the duodenum that regulates normal preasure in the common duct. The contractile value which supresses sphi:ncterotomy depends on its extension: it is almost nil in the papilla, medium in the submucuous segment and maximun in the mural segment. Section of the duodenal muscle renders the blocking agent of the Oddian cha:nnel useless.